1999
DOI: 10.1099/0022-1317-80-2-333
|View full text |Cite
|
Sign up to set email alerts
|

Two non-structural rotavirus proteins, NSP2 and NSP5, form viroplasm-like structures in vivo.

Abstract: In rotavirus-infected cells, the non-structural proteins NSP5 and NSP2 localize in complexes called viroplasms, where replication and assembly occur. Recently, we have demonstrated direct interaction of NSP5 with NSP2, and as a consequence of that, up-regulation of NSP5 hyperphosphorylation. To investigate a possible structural role for the NSP2-NSP5 interaction, we analysed the cytoplasmic distribution of the two proteins in transfected cells by immunofluorescence using specific antibodies. Here we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
248
2
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(265 citation statements)
references
References 21 publications
11
248
2
4
Order By: Relevance
“…The formation of viral inclusion bodies, or viroplasms, is a common feature of double-stranded (ds)RNA viruses from the family Reoviridae with genomes composed of 10-12 segments (Brookes et al, 1993;Fabbretti et al, 1999;Fukushi et al, 1962;Petrie et al, 1984;Rhim et al, 1962;Shikata & Kitagawa, 1977;Touris-Otero et al, 2004). These inclusion bodies are mainly composed of viral dsRNA, viral proteins and partially and fully assembled viral particles (Dales et al, 1965;Fabbretti et al, 1999;Isogai et al, 1998;Rhim et al, 1962;Silverstein & Schur, 1970;Touris-Otero et al, 2004;Wei et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of viral inclusion bodies, or viroplasms, is a common feature of double-stranded (ds)RNA viruses from the family Reoviridae with genomes composed of 10-12 segments (Brookes et al, 1993;Fabbretti et al, 1999;Fukushi et al, 1962;Petrie et al, 1984;Rhim et al, 1962;Shikata & Kitagawa, 1977;Touris-Otero et al, 2004). These inclusion bodies are mainly composed of viral dsRNA, viral proteins and partially and fully assembled viral particles (Dales et al, 1965;Fabbretti et al, 1999;Isogai et al, 1998;Rhim et al, 1962;Silverstein & Schur, 1970;Touris-Otero et al, 2004;Wei et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These inclusion bodies are mainly composed of viral dsRNA, viral proteins and partially and fully assembled viral particles (Dales et al, 1965;Fabbretti et al, 1999;Isogai et al, 1998;Rhim et al, 1962;Silverstein & Schur, 1970;Touris-Otero et al, 2004;Wei et al, 2006). In addition, the inclusion bodies have been shown to contain microtubules and thinner 'kinky' filaments suggested to be intermediate filaments (Dales, 1963;Dales et al, 1965;Spendlove et al, 1964).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in viroplasms, NSP5 interacts with other viral proteins such as NSP2 (Poncet et al, 1997;Afrikanova et al, 1998), VP1 (Afrikanova et al, 1998) and VP2 (Berois et al, 2003). The in vivo interaction with NSP2 leads to NSP5 hyperphosphorylation and the formation of viroplasm-like structures (VLSs) (Afrikanova et al, 1998;Fabbretti et al, 1999). We have recently shown that the hyperphosphorylation is the consequence of a cellular kinase that is activated by NSP5 itself in a process resembling autophosphorylation (Eichwald et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An NSP2-encoding cDNA fragment, obtained by PCR amplification using specific primers to incorporate NcoI and BamHI restriction sites at the N and C termini, respectively, was cloned into pVOTE.1 (Ward et al, 1995) to obtain the construct pVOTE.1/NSP2. Constructs pT 7 v-NSP5, pT 7 v-D1, pT 7 v-D2, pT 7 v-D3, pT 7 v-D4, pT 7 v-DT, pT 7 v-D1/D2 and pT 7 v-D4T have been described previously (Afrikanova et al, 1998;Fabbretti et al, 1999;Eichwald et al, 2002). The internal deletion plasmids pT 7 v-D2/D4T, pT 7 v-D2/D3 and pT 7 v-D3/DT were obtained by PCR using specific internal primers and cloned into KpnI and BamHI restriction sites in pcDNA3 (Invitrogen).…”
Section: Introductionmentioning
confidence: 99%